Comparison of pain control between lidocaine and prilocaine spray (TEMPE) versus lidocaine gel in the treatment of premature ejaculation: a prospective randomized controlled trial in a tertiary care centre - Nagabhairava, Manu K.; Kulkarni, Abhishek; Javali, Tarun; Sangle, Ameya R.; Patil, Amit; P. , Sandeep (International Journal of Research in Medical Sciences, 2024)
Background: Premature ejaculation is the most common cause of sexual dysfunction. There is no consensus on the treatment protocol due to poor understanding of the underlying mechanisms. Therefore, the present pilot study was conducted to compare the efficacy of topical eutectic mixture for premature ejaculation (TEMPE) spray with lidocaine gel for the treatment of premature ejaculation. Methods: After obtaining ethics approval and written informed consent, 100 patients meeting the inclusion and exclusion criteria were included. Baseline values of intravaginal ejaculation time (IELT) and international index of erectile function (IIEF) were recorded. Patients were randomly assigned into group A (lidocaine plus prilocaine spray) and group B (lidocaine gel). After 4 weeks of treatment IELT and IIEF score were recorded. The findings were noted and analysed. Results: Both the groups were similar in terms of demographic and baseline characteristics. There was a significantly higher improvement in IELT and IIEF score following treatment in group A as compared to group B. The incidence of side effects was lower in group A as compared to group B. Conclusions: We recommend that the use of TEMPE spray for the treatment of premature ejaculation as it is better than lidocaine gel.